NANOPARTICLE PREPARATION OF SNAKEHEAD FISH EXTRACT (CHANNA STRIATA) BY IONIC GELATION METHOD USING SODIUM ALGINATE AS POLYMER - TAURINA, WINTARI; ANDRIE, MOHAMAD (International Journal of Applied Pharmaceutics, 2026)
Objective: The extract from the snakehead fish (Channa striata) is a rich source of albumin, a protein recognized for its wound healing properties. In this study, we developed albumin-loaded nanoparticles using sodium alginate as the polymer matrix. We also examined how varying sonication durations affected the characteristics of the nanoparticles. Methods: Nanoparticles were prepared using ionic gelation using 0.1% sodium alginate and 0.01% calcium chloride (CaCl₂) as a cross-linker, stirred for 2 h at 1500 rpm, and sonicated for 1 h (Formula 1) or 2 h (Formula 2) using 45Hz frequency. After freeze-drying, characterization included visual appearance, %transmittance, particle size, and polydispersity index. Scanning electron microscope (SEM) and entrapment efficiency tests further evaluated the optimal formula. Results: There were notable differences in the characteristics of the nanoparticles between F1 and F2. F1 exhibited an average transmittance of 93.22%, a particle size of 606.43 nm, and a polydispersity index of 0.563. In contrast, F2 demonstrated a higher transmittance of 99.41%, a smaller particle size of 483.26 nm, and a slightly lower polydispersity index of 0.558. Statistical analysis revealed a significant difference (p<0.05) between the two formulations. F2 was identified as the optimal formulation, achieving an entrapment efficiency of 96.63%, a zeta potential of-24.6 mV, and exhibiting a wrinkled particle morphology with aggregates visible at 10.000x magnification. The optimal ultrasonication time depends on how effectively the process dissolves and distributes the ingredients evenly, as longer mixing reduces the particle size. Conclusion: Snakehead fish extract nanoparticles prepared with 0.1% sodium alginate and 2 h of sonication (F2) showed the best characteristics. After 7 days, the solution remained slightly cloudy with a few floating particles and a distinctive fish odor. The average %transmittance was 99.406%, particle size 483.266 nm, polydispersity index 0.558, zeta potential-24.6±0.294 mV, and entrapment efficiency 96.63±0.11%. SEM at 5000x and 10.000x magnification revealed mostly spherical, dense particles with rough surfaces.